(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
A Copyright is a branch of Intellectual Property Rights which can be legally characterized to be a right which gives rise to “various other bundle of rights”, such as Right to Reproduce, right to Distribute, Right to Sell etc. The focus of the law is upon preserving the ‘original works’ and the provisions ensure that the authors, creators, inventors are protected from every angle. On the other hand, the Indian Government also seeks to maintain a balance between the societal need vis-à-vis individual profits, due to which some provisions like using the work for criticism, fair use like disseminating the work for other non-profitable or for example educational purpose is exempted. But if we see the objective of copyright on the whole, it is that no other person will get the right to replicate the same work on which the Copyright has been granted, subject to some conditions which are also provided therein.